Prevalence of climacteric symptoms in menopausal and perimenopausal women - Sharma, Achala Sahai; Khan, Zareena (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: With increasing life expectancy population of menopausal women is also rising and each woman is expected to spend almost 1/3rd of her life in this phase. Due to various factors the health issues of menopausal age group are still not completely understood and addressed. Further studies in this field are expected to enhance the understanding of the subject and improve the quality of life of elderly woman. Methods: A cross sectional analysis was done over a period of one year, 200 women between 40 to 65 years of age not taking HRT and not having any other medical illness were recruited. The data regarding demography and 21 climacteric symptoms in Greene’s Climacteric Scale was collected by interviewing the subjects. The prevalence of various menopausal symptoms and their severity were analyzed. Results: Mean age of study group (n=200) was 46.8 years with menopausal group (n=79) 50.18 years and perimenopausal group (n=121) 44.6 years. Out of all 84% subjects were illiterate. The most prevalent and severe symptom was muscle and joint pain. There was no significant difference in the mean number of climacteric symptoms in various demographic groups and between menopausal and perimenopausal group. Conclusions: The climacteric symptoms do not appear to decrease in number or intensity after transition from perimenopause to menopause. Differences in sensitivity, literacy, social and cultural factors etc. among elderly women may be responsible for under reporting or differences in reporting. Exploring the issues of menopausal health and training of health personnel in this field may improve awareness of these women about various menopause related health issues and thus improve their quality of life.